5 year-analysis of reported dog bites in Baghdad city - Thabit, Maral Fathalla (AL-Kindy College Medical Journal, 2012)
Background: Animal bites in humans are an important public health problem. Most of these bites are dog bites. Dog bites in humans are a complex problem embracing public health and animal welfare, both in developed and developing nations. .Al-kindy Col Med J Vol.8 No.2 2012 P: 149Objectives: in order to estimate the magnitude of the problem and to understand the epidemiological characteristics of dog bite victims registered in Baghdad city regarding their age, sex, number of registered dog bite victims per month and year along the studied period ( 2006-2010) and also to sniff out any seasonal variation in dog bite attacks .Methods: A across-sectional study was carried out during January (2011), in the Anti-Rabies clinic of (Pasteur Institute) .Data pertaining to victims was collected from the registered monthly reports from January 1, 2006 and December31, 2010.Results: The total number of registered dog bite victims per 5 years of the study was equal to 26795. The studied epidemiological characteristics showed highly significant differences towards male victims with monthly mean number (60.381), the age group (15-45) years as people at risk with monthly mean number (95.167) , the highest total number of registered dog bite victims during the year (2009), with a monthly mean number (56.056), also there was an evident increase in the number of dog bite attacks during the warm months (May and June) with a monthly mean number ( 50.82) Conclusion: The persistence of dog bite as public health problem in Baghdad city.